Skeletal muscle atrophy in advanced interstitial lung disease. Issue 6 (17th June 2015) - Mendes, Polyana; Wickerson, Lisa; Helm, Denise; Janaudis‐Ferreira, Tania; Brooks, Dina; Singer, Lianne G.; Mathur, Sunita
Abstract Background and objective A limited number of studies examine skeletal muscle dysfunction in individuals with interstitial lung disease (ILD). We compared upper and lower limb muscle size and strength in individuals with advanced ILD with healthy controls. Second, the relationships of muscle size to muscle strength and function were explored. Methods Individuals with advanced ILD listed for lung transplant and healthy control subjects were studied. B‐mode ultrasound was performed to assess cross‐sectional area (CSA) of rectus femoris and thickness of gastrocnemius and soleus and biceps brachii. Subjects performed isometric muscle strength testing, Short Physical Performance Battery, Timed Up and Go, and Unsupported Upper Limb Exercise Test. Results Twenty‐six individuals with advanced ILD (61 ± 8 years; 73% males; forced vital capacity: 2 ± 0.8 L, 49 ± 13% predicted; diffusing capacity of carbon monoxide: 9.3 ± 4 mL/min/mm Hg, 51 ± 20% predicted) and 12 healthy age and gender‐matched controls (56 ± 9.5 years; 50% males) were included. Compared with controls, people with ILD had a smaller CSA of rectus femoris (7.6 ± 2.1 vs 9.4 ± 2.4 cm2; P = 0.03) and lower strength of knee extensors (119 ± 35 vs 147 ± 39 Nm; P = 0.02) and plantarflexors (37 ± 19 vs 50 ± 15 Nm; P = 0.02), but not of biceps. Individuals with ILD also had impaired performance on all functional tests (P < 0.02). Moderate correlations were found between rectus femoris CSA and knee extensor strength (r = 0.63; P < 0.01) and biceps thickness and elbow flexor strength (r = 0.78; P < 0.01) in the ILD group. Conclusions Individuals with advanced ILD presented with lower limb muscle atrophy and weakness. Future studies should evaluate the effectiveness of exercise training on muscle function in advanced ILD.